1993
DOI: 10.2514/3.11666
|View full text |Cite
|
Sign up to set email alerts
|

Application of scalar implicit approximate factorization for underwater magnetohydrodynamic propulsion concept analyses

Abstract: Numerical procedures have been developed to analyze multidimensional flow and imposed electromagnetic fields associated with a marine magnetohydrodynamic (MHD) propulsion concept. Chorin's artificial compressibility treatment is applied to determine the incompressible flowfield both internal and external to the MHD thruster, using a zonal formulation. Both inviscid and viscous flow are considered. Determination of three-dimensional magnetic, electric, and Lorentz force fields is based on suitable idealizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The details of the numerical scheme for the threedimensional Navier-Stokes equations can be found in Refs. [8][9][10][11]. Some of the unique features of the scheme are described here.…”
Section: Methodsmentioning
confidence: 97%
“…The details of the numerical scheme for the threedimensional Navier-Stokes equations can be found in Refs. [8][9][10][11]. Some of the unique features of the scheme are described here.…”
Section: Methodsmentioning
confidence: 97%
“…Concerning the issue of end losses, the authors have seriously considered the effects of end losses in their analysis. Preliminary results from an analysis of end effects have previously been published [2]. The results of these efforts have shown that the magnitude of end losses that might be expected for a well designed, annular thruster are much smaller than for a linear generator or accelerator.…”
Section: Thrustermentioning
confidence: 99%
“…In the field of marine propulsion, perhaps one of the first related patents and manuscripts dates back to 1960s. [23][24][25] Many numerical 21,26,27 and analytical 28,29 simulations as well as experimental [29][30][31][32][33][34][35][36][37] studies have been conducted by some researchers investigating the effects of MHD channel shapes, 27,29 electric and magnetic field strength and patterns (continuous/alternating), 21,32 water conductivity enhancement, 34,37 super-conduction and cooling systems, 30,31,35 and also stability issues 28 on the electro-magnetic thrust production and efficiency of the system. A comprehensive review of this field has been presented by Weier et al 38 In the present paper, a set of parametric studies is conducted on different aspects of a planar MHD propulsion system and their effects on its electromagnetic thrust, efficiency, and heat transfer.…”
Section: Introductionmentioning
confidence: 99%